ANTARA MASA ORDE BARU DAN MASA REFORMASI DALAM PERKEMBANGAN HUKUM TERHADAP PERLINDUNGAN PEREMPUAN - Dinnar Ajeng Ravianti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
In the International Human Rights Agreement prohibiting discrimination against women has been ratified by 169 countries (Universal Declaration of Human Rights). Article 1 paragraph (3) and the 1945 Constitution, which reads "(3) The State of Indonesia is a state of law" which means an ideal home for human rights where only in this rechtsstaat there is a guarantee of human rights such as judicial independence, fair legal process, judicial review. The problem of how the law developed regarding the protection of women between the New Order and the reform era, then by conducting normative legal research where the approach used is legislation, the results obtained that on a scale of 1-10 there are aspects of respect, protection and fulfillment of human rights only at 5.40% as well as the right to be free from torture which is at 5.02% where both variables are certainly a reflection of the protection of women's rights themselves. In addition, the Legal State Index surveyed by the World Justice Project from 2015-2023 means that after the reform era it tends to stagnate regarding the increase in its democracy rate. At the process level, discriminatory practices still occur widely, the main cause being the economic and social status of those seeking justice. Although the courts are considered relatively responsive to women as victims of violence. However, access to the community is still narrow.